Case study in Poland: understanding spatial diversity of social vulnerability to natural hazards based on local level assessments within the European Union - Rucińska, Dorota; Adinolfi, Giovanna; Frigerio, Ivan; Gavinelli, Dino; Zanolin, Giacomo; Werner, Welf; Rauscher, Natalie; Jaczewska, Barbara; Gręda, Łukasz (International journal of disaster risk reduction, 2023)
Social vulnerability is an element of disaster risk theory and reduction, a tool to understand and improve risk mitigation. The paper focusses on social vulnerability to multi-hazards within the EU on Central and Southern Europe but not including physical factors; within Poland, this quantification type is as yet unavailable. Based on the knowledge and social vulnerability estimations in selected countries within the European Union and the US, it shows the Social Vulnerability to Natural Hazards index to unify these approaches. One case study in Poland, which included careful study of the national database, revealed the problems of collecting useful data in order to study social vulnerability within municipalities. But it also indicated a useful variable when placing a social vulnerability assessment. The paper shows maps within the most vulnerable municipalities in Poland by percentage share, with 41.8% urban and 41.46% urban-rural municipalities showing the highest value of social vulnerability based on this comprehensive index. It also indicates the need to take locally better-targeted and diverse policy and actions for risk reduction using social vulnerability in the type of municipality. Such a richness of approaches with a simultaneous diversity of used variables could be due to a lack of any homogeneous data collected for municipalities within EU states. So we suggest there is a need to build a unified database in Europe in order to estimate social vulnerability in municipalities. It is a basic requirement when it comes to comparing disaster risk reduction progress and effectiveness in the EU.